2009
DOI: 10.1016/j.virol.2009.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of the left origin of lytic replication of murine gammaherpesvirus 68

Abstract: Murine gammaherpesvirus 68 (MHV-68) replicates robustly in cell culture, providing a model for studying viral genome replication during de novo infection of tumor-associated herpesviruses. We have previously identified a 1.25-kb origin of lytic replication (oriLyt) for MHV-68. To further investigate the molecular mechanism of viral genome replication, we first fine-mapped essential cis-elements from this oriLyt fragment using a transposon-mediated high-density mutagenesis method. The result provided informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…By EMSAs, the second CCAAT box of Ori-L1 is essential for C/EBP binding, whereas the first CCAAT box is dispensable (Wu et al, 2003). Our group revealed that CCAAT boxes are essential ciselements for the function of the MHV-68 left oriLyt (Gong et al, 2009). To investigate whether the CCAAT boxes in the MHV-68 oriLyt core region are also important for C/EBP binding, we designed eight oligonucleotides based on L1 + 2, L3 + 4, R1 + 2, and R3 + 4; each of them contained mutations in one CCAAT box (Fig.…”
Section: C/ebps Bind To Orilyts In the Mhv-68 Genome During De Novo Imentioning
confidence: 84%
See 4 more Smart Citations
“…By EMSAs, the second CCAAT box of Ori-L1 is essential for C/EBP binding, whereas the first CCAAT box is dispensable (Wu et al, 2003). Our group revealed that CCAAT boxes are essential ciselements for the function of the MHV-68 left oriLyt (Gong et al, 2009). To investigate whether the CCAAT boxes in the MHV-68 oriLyt core region are also important for C/EBP binding, we designed eight oligonucleotides based on L1 + 2, L3 + 4, R1 + 2, and R3 + 4; each of them contained mutations in one CCAAT box (Fig.…”
Section: C/ebps Bind To Orilyts In the Mhv-68 Genome During De Novo Imentioning
confidence: 84%
“…We first cloned the CHOP10 sequence into pCMV-HA to generate pCMVHA-hCHOP10 and confirmed the expression of hCHOP10 by western blotting (data not shown). We then co-transfected pMOL (bearing the 1.1-kb MHV-68 left oriLyt) (Gong et al, 2009) and pCMVHA-hCHOP10 (or pCMV-HA as a vector control) into 293T cells. Twenty four hours later, we infected cells with MHV-68 to provide trans-factors required for DNA replication and prepared total cellular DNA for Southern blotting.…”
Section: C/ebps Bind To Orilyts In the Mhv-68 Genome During De Novo Imentioning
confidence: 99%
See 3 more Smart Citations